The Role of Ursodeoxycholic Acid Administration During the COVID-19 Pandemic: A Questionnaire Survey - Cheng Zhou; Ran Jia; Jinqiu Yang; Tong Liu; Xiaoyan Liu; Lin Yang; Wenxia Zhao (Canadian Journal of Infectious Diseases and Medical Microbiology)
In December 2022, China classified COVID-19 as a category B infectious disease. This ended 2 years of close epidemiological surveillance of COVID-19. The objective of this questionnaire was to assess the infection status in the COVID-19 pandemic since December in Henan Province, China, and the prevalence of infection in people who were taking ursodeoxycholic acid (UDCA) during this period. We distributed questionnaires to patients attending the gastroenterology clinic at the First Affiliated Hospital of Henan University of Chinese Medicine. The questionnaire lasted for 3 weeks and a total of 660 were collected, of which the number of people taking UDCA was 70. This is the first investigation into the rate of infection among those taking UDCA during the time of the COVID-19 pandemic. Our results showed that the overall infection rate among those taking UDCA was 71.43% (n = 50), with a 10% (n = 7) rate of asymptomatic infections, which was significantly lower than the 85.42% (n = 504) and 6.27% (n = 37) rates among respondents who did not take. The administration of UDCA showed a trend toward reducing the rate of COVID-19 infection, but the difference was not statistically significant when compared to patients with shorter durations of medication use. While less than 30% of participants remained uninfected during the study period, indicating a potential protective effect, it is important to note that complete prevention of SARS-CoV-2 infection by UDCA was not observed.